Pelestarian Ekosistem: Urgensi Pengaturan Sanksi Pemulihan Bagi Spesies dalam Kejahatan terhadap Satwa Liar - Utami, Britha Mahanani Dian (UI Scholars Hub, 2023)
Law Number 5 of 1990 concerning the Conservation of Natural Resources and Ecosystems has never been revised while the development of science and technology has influenced a paradigm shift in the protection of biodiversity. The proposal of Commission IV of the House of Representatives to propose a revision of Law Number 5 of 1990 was approved in the Plenary Session as a 2021 Priority Bill. However, in the draft Biodiversity Conservation Bill, recovery is still oriented towards the recovery of the area, while not yet regulating recovery for species that are victims of crime. This paper argues that the regulation of recovery sanctions for species in cases of wildlife crime is a must, because of two main things, namely first, the recognition of animal legal rights requires the state to formulate legal rules that are more favorable and see legal protection solely aimed at the interests of animals. Secondly, wildlife is part of the ecosystem components, which are interdependent, and if it is taken from nature, there must be actions to recover it and return it to nature so that the ecosystem cycle is restored. The regulation of sanctions for species recovery should at least explicitly stipulate that the responsibility for the cost of species recovery should be attached to the perpetrator.